Educational Game-Based Mathematics Learning Media for Elementary School Children - Agustinus Sirumapea; Ferawati Ferawati; Fiqih Hana Saputri; Andhika Fajar Utama (Institut Teknologi dan Bisnis Bina Sarana Global, 2023)
This study aims to produce and test the feasibility of an educational game for Mathematics using Construct 2 software. This game contains Mathematics subject matter and is used as a learning medium at SDIT Smart Syahid. The research method used in making this Educational game is ADDIE (Analysis – Design- Development – Implementation – Evaluation), where the research stages are in the form of needs analysis, design process, product development, implementation, and evaluation. The analysis phase includes a needs analysis related to the product. The stages in the design process include the design process and making improvements if there are still design discrepancies between the user and the analyst. The product development stage contains manufacturing based on the analysis and design results that have been done before. Next is the implementation stage; at this stage, the programmer develops the design into a program that can be tested. The last step is the evaluation stage and making improvements if there are still design discrepancies between the user and the analyst. From the results of this study, the researcher succeeded in creating a Mathematics educational game.